2019
DOI: 10.1161/hypertensionaha.119.12697
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Outcomes With Intensive Blood Pressure Targets in Chronic Kidney Disease Patients

Abstract: Hypertension is highly prevalent and morbid in the chronic kidney disease population, and blood pressure (BP) targets for this population are unclear. We aimed to compare all-cause mortality outcomes with intensively targeting systolic BP to <130 mm Hg versus a standard of <140 mm Hg. Individual patient data from 4983 chronic kidney disease patients with hypertension were pooled from 4 multicenter randomized control trials—AASK (African American Study of Kidney Disease and Hypertension), ACCORD (Action t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 29 publications
1
33
0
2
Order By: Relevance
“…Both of these methods found in the SPRINT data a relationship between kidney health and the treatment effect that has also been identified by other researchers. 32 An important next step is confidence interval construction. We have developed causal MARS so that it would be conducive to confidence interval construction, but we leave this task to future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these methods found in the SPRINT data a relationship between kidney health and the treatment effect that has also been identified by other researchers. 32 An important next step is confidence interval construction. We have developed causal MARS so that it would be conducive to confidence interval construction, but we leave this task to future work.…”
Section: Discussionmentioning
confidence: 99%
“…They found that intensive blood pressure management does not improve primary outcomes for patients with CKD. 32 Something that the authors do not address is why they chose to analyze patients with CKD. Presumably, they used some combination of prior medical knowledge and manual hypothesis selection.…”
Section: Real-data Applicationsmentioning
confidence: 99%
“…The evidence on the BP target in CKD patients is derived from four main sources: (a) ad hoc analyses of randomized clinical trials (RCTs) designed for renal outcomes, (b) observational follow‐up of these RCTs, (c) post hoc analyses of other RCTs, (d) meta‐analyses of individual or aggregate data from RCTs 4‐12 . Table 1 presents such key studies comparing intensive vs standard BP lowering arms 4‐12 . There is considerable heterogeneity among these studies in sample size, patients’ characteristics, BP measurement methodology, duration of follow‐up, examined end points (renal, cardiovascular, mortality and composite end points).…”
Section: Study Design N Population Follow‐up (Y) Achieved Bp Standamentioning
confidence: 99%
“…In a meta‐analysis of individual data from 4983 CKD hypertensive patients pooled from four RCT, including the AASK, ACCORD (Action to Control Cardiovascular Risk in Diabetes), MDRD, and SPRINT, the all‐cause mortality rate trended toward improved outcomes with intensive antihypertensive treatment, yet this difference did not reach statistical significance 12 . However, after excluding patients with GFR ≥60 mL/min/1.73 m 2 and those on intensive glycemic control, there was a statistically significant decrease in all‐cause mortality rate 12 .…”
Section: Study Design N Population Follow‐up (Y) Achieved Bp Standamentioning
confidence: 99%
See 1 more Smart Citation